Rumen-Protected Fat and Rumen-Protected Choline Co-Supplementation: Impacts on Performance and Meat Quality of Growing Lambs - Haitao Liu; Fadi Li; Fei Li; Zhiyuan Ma; Tao Wang; Qinwu Li; Xinji Wang; Kaidong Li (Veterinary Sciences)
This study aimed to assess the effect of co-supplementing rumen-protected fat and rumen-protected choline on growth performance, carcass traits, and meat quality in lambs. Using a randomized experimental design, 45 weaned female Tian×Hu crossbred lambs (3 months old; average body weight: 27.34 ± 0.57 kg, mean ± SD) were randomly allocated to one of three dietary treatment groups. The three dietary treatments were as follows: a basal diet group (CON), a group receiving 2% rumen-protected fat in place of 2% barley (RPF), and a group supplemented with 2% rumen-protected fat and 0.4% rumen-protected choline, replacing 2% barley and 0.4% corn germ in the basal diet (RPFC). Compared to the CON group, neither the RPF nor RPFC treatments resulted in significant differences in growth performance (p > 0.05). However, the RPFC group showed a 5.3% increase in dry matter intake (DMI) compared to the RPF group (p < 0.05). Compared with the CON, the RPF treatment increased 69.23% the relative abundance of C18:2n-6t (p < 0.05), but the content of C17:0, C17:1, C18:1n-9c, and iso-C18:0 in Longissimus lumborum was decreased by 16.49%, 15.78%, 6.45% and 27.78%, respectively (p < 0.05). The RPFC treatment increased the relative abundance of C16:1 in Longissimus lumborum (p < 0.05). The RPF and RPFC treatments significantly increased serum levels of high-density lipoprotein (HDL) and total cholesterol compared to the CON group (p < 0.05). The RPF treatment raised HDL by 50.00% and total cholesterol by 38.03%, while the RPFC treatment increased HDL by 39.47% and total cholesterol by 26.03%. Furthermore, compared to the RPF group, the RPFC treatment led to a 13.47% increase in the 45 min b* color value of the Longissimus lumborum (p < 0.01) and a significant 45.45% reduction in the relative abundance of C18:2n-6t fatty acid in the same muscle (p < 0.05). In summary, rumen-protected choline reduces the negative effects of rumen-protected fat on feed intake in lambs and changes fatty acid profile in meat.